Surrogate endpoints: when to use and when not to use? A critical appraisal of current evidences - PEDRAZZI Vinicius; Fellipe Augusto Tocchini de FIGUEIREDO; Larisse Eduardo ADAMI; Flávia FURLANETO; Daniela Bazan PALIOTO; Michel Reis MESSORA (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract Clinical research needs to formulate a question, which must be answered by obeying ethical precepts with well-defined inclusion/exclusion criteria and approval of the study on platforms of ethical appreciation and clinical trial records. In comparing the results or clinically relevant outcomes should be prioritized in the study of techniques, products, inputs, drugs and therapies. However, it is not always possible to use long study drawings, with many participants, and with many costs, then look for study designs with surrogate outcomes, usually a shorter path, with less sample size and considerably lower costs to the research, with shorter intervention time. Considering these outcomes as major challenges in clinical research, the premise of this work was to examine in relevant research platforms, studies on the feasibility of using surrogate endpoints for clinically relevant parameters in dentistry, with a critical evaluation of the advantages, disadvantages, and need for validation of substitute parameters for clinical studies. After a critical analysis of the results, it could be concluded that surrogate endpoints may have an important role in the initial process of developing new drugs, faster, with less sampling, and lower risk of side effects for the patient. Careful use of the surrogate endpoints is advised because, even if validated, they can provide ambiguous evidence and not be extrapolated to other populations, and may lead to bias due to the individual interpretation of each researcher. The use of unplanned surrogate outcomes that arise during the study requires a lot of caution.